KRITERIA VISIBILITAS HILAL DALAM PENETAPAN AWAL BULAN KAMARIAH DI INDONESIA - Suhardiman, Suhardiman (The Pontianak State Institute of Islamic Studies, 2013)
To determine the start of lunar months, there are several methods that serve as the basis, among others by using the methods of hisab (calculation) and rukyat (new moon sighting). Actually, both hisab and rukyat have the same goal, namely hilal. Therefore, the two methods do not need to be disputed any more. In fact they complement each other. Calculation of the correct and accurate reckoning will certainly be proven by rukyat anyway. However, the problem remain for Muslims today is the critera imkan ar-rukyat (visibility of the new moon) used. If these problems can be overcome, then it is certain that Muslims are no longer stuck with the difference of opinions and views from many quarters about the determination of the beginning of the month, when the hilal is on a